Distributional health and financial consequences of increased cigarette tax in Iran: Extended cost-effectiveness analysis - Behzad Raei; Sara Emamgholipour; Amirhossein Takian; Mehdi Yaseri; Ghahreman Abdoli; Ahad Alizadeh (Health Economics Review, 2021)
Background: To assess the potential impact of a tax-induced cigarette price increase on financial and health outcomes by different socioeconomic groups. Methods: In a modeled condition using pooled cross-section data from Household Income and Expenditure Survey (2002-2017) and Iran 2019 population data, a methodology of an extended cost effectiveness analysis (ECEA) was applied to model the impact on cigarette consumption of hypothetically increased cigarette tax. The methodology was employed to evaluate: [1] health benefits (premature deaths averted); [2] health expenditures regarding smoking-related disease treatment averted; [3] additional tax revenues raised; [4] change in household expenditures on cigarettes; and [5] financial risk protection among male Iranian smokers in a time span of 60 years following a one-time increase in cigarette price of 75%. The Stata version 15.1 (StataCorp., College Station, TX, USA) was used to perform the relevant analysis and estimate regression models. Results: A 75% increase in cigarettes price through taxation would reduce the number of smokers by more than half a million, 11% of them in the poorest quintile; save about 1.9 million years of life (11% of which would be gained in the lowest quintile compared to 20% in the highest one); eliminate a total of US196.4 million of health expenditures (9% of which would benefit the bottom quintile). Such a policy could raise the additional annual tax revenues by roughly US 1 billion, where the top two quintiles bear around 46% of the total tax burden. We estimated that the tax increase would avert an estimated 56,287 cases of catastrophic expenditure that wholly concentrated among the bottom two expenditure quintiles. Conclusion: Increasing cigarette tax can provide health and financial benefits, and would be pro-poor in terms of health gains, Out-of-Pocket (OOP) savings, and financial risk protection against smoking-related diseases.
Keywords: 330; Taxes; Elasticity; Cigarette smoking; Outcome assessment